Universality Classes of Magnetic Domain Wall Motion - Lee, Jae-Chul; Kim, Kab-Jin; Ryu, Jisu; Moon, Kyoung-Woong; Yun, Sang-Jun; Gim, Gi-Hong; Lee, Kang-Soo; Shin, Kyung-Ho; Lee, Hyun-Woo; Choe, Sug-Bong (AMER PHYSICAL SOC, 2011)
We examine magnetic domain wall motion in metallic nanowires Pt-Co-Pt. Regardless of whether the motion is driven by either magnetic fields or current, all experimental data fall onto a single universal curve in the creep regime, implying that both the motions belong to the same universality class. This result is in contrast to the report on magnetic semiconductor (Ga,Mn) As exhibiting two different universality classes. Our finding signals the possible existence of yet other universality classes which go beyond the present understanding of the statistical mechanics of driven interfaces.
Keywords: DYNAMICS; CREEP; CRITICALITY; NANOWIRES; BEHAVIOR; FILM